AKTIVISME GREENPEACE DALAM MENDORONG PERUSAHAAN SHELL BERKONTRIBUSI PADA PERJANJIAN PARIS - Nazlatunnuha, Dinda Fitri (Indonesian Journal of International Relations, 2024)
This research examines Greenpeace's activism in encouraging the Shell company to contribute to the 2015 Paris Agreement, and the power of Greenpeace as an INGO in that case. Through the concept of the main function of non-governmental organizations according to Glasius, Kaldor, and Anheier as an analytical tool as well as the concept of the power of non-governmental organizations according to BostrÃ¶m & HallstrÃ¶m. This research is described using descriptive and qualitative methods, as well as documentation studies which produce the argument that Greenpeace carries out its function as activism which acts as an "alarm" for the global corporation Shell to contribute to the 2015 Paris Agreement. In its advocacy efforts to sue Shell, Greenpeace achieved victory over collective demands. The alliance, in this case, cannot be separated from the power possessed by Greenpeace as an NGO, namely symbolic power, social power, cognitive power and supervisory power